Integration of Religious Moderation Based on Socio-Cultural and Religious Values in the Curriculum of Educational Institutions - Bakar, Abu; Prastyo, Angga Teguh; Lestantyo, Prayudi (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3242, 2024)
Most of the intolerance issues in Indonesia are due to the lack of a comprehensive understanding of the urgency of maintaining social diversity among different ethnicities and religious adherents. This study argues that the application of religious moderation by involving socio-cultural and religious values will be able to make religious moderation in line with the values faced by the local community. Therefore, the study formulates that the principles of socio-cultural and religious values will strengthen religious moderation at the level of education and the wider community because they have great relevance and impact on social development. This study uses a qualitative method with a case study approach in educational institutions in Bali which explains in detail the implementation of social and cultural-based religious moderation in educational institutions. The results of the study show that (1) the existence of religious moderation material based on social and cultural values is able to form agreements and shared understanding among students to care about tolerance and peaceful life in their environment. (2) Socio-cultural and religious values can be used as an enrichment of religious moderation material in schools and other educational institutions. The implications of the use of socio-cultural and religious values in the development of religious moderation are able to make religious moderation more actual and relevant to students' lives in responding to social issues and religious fundamentalism.